2003
DOI: 10.1001/archneur.60.4.545
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Pattern of Olfactory Deficits in Parkinson Disease Using the Brief Smell Identification Test

Abstract: With the use of the B-SIT, 5 specific odors appear primarily affected in patients with Parkinson disease. Significantly, the ability of patients to detect some odors was unimpaired compared with that of controls. Better diagnostic aids could be developed on the basis of the selective pattern of hyposmia observed in Parkinson disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
96
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(109 citation statements)
references
References 24 publications
12
96
0
1
Order By: Relevance
“…In contrast to this finding, Hawkes and Shephard (1993) suggested that PD patients might have a specific anosmia. Supporting these findings, Daum et al (2000), Double et al (2003), and Silveira-Moriyama et al (2005) obtained similar results to those of Hawkes and Shephard (1993). However according to one of the recent reports on PD and specific hyposmia/anosmia, Haehner et al (2013) showed that there is no specific hyposmia in PD.…”
Section: Introductionmentioning
confidence: 54%
“…In contrast to this finding, Hawkes and Shephard (1993) suggested that PD patients might have a specific anosmia. Supporting these findings, Daum et al (2000), Double et al (2003), and Silveira-Moriyama et al (2005) obtained similar results to those of Hawkes and Shephard (1993). However according to one of the recent reports on PD and specific hyposmia/anosmia, Haehner et al (2013) showed that there is no specific hyposmia in PD.…”
Section: Introductionmentioning
confidence: 54%
“…The study done by Doty et al (1992) [15] also could not find relation between UPSIT score with stage of the patient. The study done by Double et al (2003) [11] reported no interaction between B-SIT score and PD severity. In their study, 16 of 20 patients (80%) of stage 1; 16 0f 20 patients (80%); and 8 of 9 patients (89%) had abnormal olfaction.…”
Section: Observations and Resultsmentioning
confidence: 87%
“…Olfactory function was assessed by means of odor detection, odor discrimination, and an odor identification task. Tests of olfaction are commonly based on total olfactory performance after exposure to multiple odors [11]. The nose was checked for patency and all patients had intact nasal passages.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Olfactory dysfunction might be selective for specific odors, as has been suggested in studies of the Caucasian population [22,23]. One previous study from Germany reported that licorice, banana, aniseed, pineapple, apple, and turpentine are the best odors for discriminating PD from controls [24], while an Australian study suggested that the five odors pineapple, banana, gasoline, smoke, and cinnamon have the best discriminatory value for PD [25]. One American study found that the three odors banana, licorice, and dill pickle have high accuracy for the diagnosis of PD [22].…”
Section: Discussionmentioning
confidence: 95%